Spirituality/religiosity, substance use, and HIV testing among young black men who have sex with men. (1st May 2017) - Carrico, Adam W.; Storholm, Erik David; Flentje, Annesa; Arnold, Emily A.; Pollack, Lance M.; Neilands, Torsten B.; Rebchook, Gregory M.; Peterson, John L.; Eke, Agatha; Johnson, Wayne; Kegeles, Susan M.
Highlights: Large sample of 1595 young black men who have sex with men. Examines facets of spirituality/religiosity as correlates of substance use and HIV testing. Binge drinking is independently associated with 29% lower odds of recent HIV testing. Abstract: Background: Spirituality and religiosity may serve as both a resource and a barrier to HIV prevention with young black men who have sex with men (YBMSM). We examined indices of spirituality/religiosity as correlates of binge drinking, stimulant use, and recent HIV testing in a sample of YBMSM. Methods: From 2011–2013, annual venue-based surveys of sexually active YBMSM ages 18–29 were conducted in Dallas and Houston, Texas. Binge drinking and stimulant use were assessed in the past two months. Participants recently tested for HIV (i.e., within the past six months) were compared to those without recent HIV testing (i.e., never tested or tested more than six months ago). Results: Among the 1565 HIV-negative or HIV-unknown YBMSM enrolled, more engagement in spiritual and religious activities was associated with greater odds of reporting stimulant use (Adjusted Odds Ratio [AOR] = 1.20; 95% CI = 1.04–1.40) while higher spiritual coping was associated with lower odds of reporting stimulant use (AOR = 0.66; 95% CI = 0.56–0.78). Binge drinking was independently associated with 29% lower odds of recent HIV testing (AOR = 0.71; 95% CI = 0.55–0.92), but lower odds of binge drinking did not mediate the association of engagement in spiritual and religious activities with 27% greater odds of recent HIV testing (AOR = 1.27; 95% CI = 1.11–1.46). Conclusions: Among YBMSM, culturally tailored approaches addressing spirituality/religiosity could support prevention of stimulant use and increase HIV testing. In particular, expanded efforts are needed to promote HIV testing in binge drinkers.